Distribuição e diversidade de herbáceas de sub-bosque em uma floresta de terra firme da Amazônia Meridional - Santos, Eliana Celestino da Paixão Rodrigues dos (2012)
Environmental heterogeneity is a determining factor of the structure of biological communities. Thus, understanding the distribution of species along environmental gradients provides assistance to conservation. The goal of this study was to determine the distribution pattern of the herbaceous community in three areas of the Southern Amazon. Sampling was conducted in three modules totaling 39 permanent plots according to the protocol of collection of the Program for Research in Biodiversity. All herbaceous and ground hemiepiphyte subjects above 5 cm were recorded. Multivariate analyses were used to summarize the species composition, multiple regression models were used to determine if environmental variables and disturbance caused by logging influenced the composition of the herbaceous community. We recorded 7.965 individuals representing 70 species. The distance of the water course was the main factor associated with the distribution of the species, interactions between variables showed that canopy openness and sand content also influence the species composition, and there was no effect in the number of trees cut. Species richness increased in areas where canopy cover was higher and it decreases as it becomes more distant from the watercourse. The occurrences of preferred habitats for some species have, in addition to an ecological interest, a practical significance for the conservation and management of these species. Currently, the area of preservation of streams provided by the Forest Code in effect is 30 m for rivers up to 10 m wide. However, this study shows that the range of protection should be extended to at least 100 m wide.